ANNUAL REPORT OF THE CENTRAL INLAND FISHERIES RESEARCH INSTITUTE, BARRACKPORE FOR THE YEAR 1960-61 - Barrackpore, Central Inland Fisheries Research Instit (Indian Journal of Fisheries, 2011)
Substantial progress was achieved during the year in all investigationsundertaken by the Research Institute. There was also an all-round expansionof activities of the various sections and units, under both normal andSecond Five-Year Plan programmes.During the year under report, 6 additional residential quarters were constructedat Barrackpore at a cost of Rs. 1,22,200. An area of 35-25 acres ofland was acquired for the establishment of an experimental fish farm in Kakdwip.The construction of Garage, Workshop and Stores at Headquarterswas sanctioned at an estimated cost of Rs. 1,31,000. Sanction for the constructionof an aquarium at a cost of Rs. 99,615 has also been received fromthe Government. 'The draft proposals for the implementation of the Third Five-Year Planprogramme were submitted to Government.The following Officers were appointed